Genotype MTBDR plus assay for molecular detection of rifampicin and isoniazid resistance in Mycobacterium tuberculosis - Soniya Sharma; Molly Madan; Charu Agrawal; Ashish K Asthana (Wolters Kluwer Medknow Publications, 2014)
Aim: This study was performed for the rapid identification of Mycobacterium tuberculosis complex and its resistance to rifampicin and isoniazid, directly from the sputum samples of pulmonary tuberculosis patients. Materials and Methods: A commercially available genotype MTBDR plus assay was used for the identification and detection of mutations in Mycobacterial isolates. A total of 100 sputum samples of pulmonary tuberculosis patients were analyzed by using the genotype MTBDR plus assay. The MTBDR plus assay is designed to detect the mutations in the hotspot region of rpoB gene, katG and regulatory region of inhA gene. Results: The genotype MTBDR plus assay detected 22% multidrug resistant (MDR), 2% rifampicin (RMP) monoresistant and 1% isoniazid (INH) monoresistant isolates. In 22 MDR isolates, the codons most frequently involved in RMP-associated mutations were codon 531 (54.55%), 516 (31.82%) and 526 (13.63%), and 90.90% of MDR isolates showed KatG S315T mutations and 9.1% showed inhA C-15T mutations associated with INH resistance. Conclusion: The new genotype MTBDR plus assay represents a rapid, reliable tool for the detection of MDR-TB, wherein results are obtained in 5 h allowing early and appropriate treatment, which is essential to cut the transmission path and reduce the spread of MDR-TB. The genotype MTBDR plus assay can readily be included in a routine laboratory work for the early diagnosis and control of MDR-TB.